Recyclable and biocompatible microgel-based supporting system for positive 3D freeform printing of silicone rubber - Tan, Wen See (2022)
Additive manufacturing (AM) of biomaterials has evolved from a rapid prototyping tool into a viable approach for the manufacturing of patient-specific implants over the past decade. It can tailor to the unique physiological and anatomical criteria of the patient's organs or bones through precise controlling of the structure during the 3D printing. Silicone elastomers, which is a major group of materials in many biomedical implants, have low viscosities and can be printed with a special AM platform, known as freeform 3D printing systems. The freeform 3D printing systems are composed of a supporting bath and a printing material. Current supporting matrices that are either commercially purchased or synthesized were usually disposed of after retrieval of the printed part. In this work, we proposed a new and improved supporting matrix comprises of synthesized calcium alginate microgels produced via encapsulation which can be recycled, reused, and recovered for multiple prints, hence minimizing wastage and cost of materials. The dehydration tolerance of the calcium alginate microgels was improved through physical means by the addition of glycerol and chemical means by developing new calcium alginate microgels encapsulated with glycerol. The recyclability of the heated calcium alginate microgels was also enhanced by a rehydration step with sodium chloride solution and a recovery step with calcium chloride solution via the ion exchange process. We envisaged that our reusable and recyclable biocompatible calcium alginate microgels can save material costs, time, and can be applied in various freeform 3D printing systems.